Improving energy efficiency of power electric power plants of low-tonnage passenger ships - А. F. Burkov; V. V. Mikhanoshin; V. K. Nguyen (Омский научный вестник)
The article is devoted to solving the problem of improving the energy efficiency of power plants of high-speed lowtonnage (planing) vessels used for passenger transportation between coastal settlements on the example of the port of Vladivostok located on the Muravyov-Amursky Peninsula, which has mainly land communication with settlements located on the coast. The oversaturation of motor transport, due to the need for communication between localities, which are usually characterized by dense buildings, is one of the main causes of many hours of traffic congestion, which worsen the environmental situation and increase social tension in society. At the same time, the tourist attractiveness of Primorye is also decreasing. One of the promising areas for solving this transport problem is the use of low-tonnage passenger vessels, in particular planing vessels, with hybrid electrified power propulsion systems. According to the available data, such vessels have reduced consumption of fuel and lubricants necessary for the operation of power plants and reduction in harmful emissions into the surrounding atmosphere by more than two times compared to similar traditional diesel vessels. In addition, the prospects of the proposed scientific and technical solution are due to the reduction in the time of passenger transportation while reducing the cost of travel.